2018
DOI: 10.24200/sci.2018.20888
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tissue Constitutive Material Models and the Finite Element Analysis of Blast-Induced Traumatic Brain Injury

Abstract: Abstract. Traumatic Brain Injury (TBI) often occurs due to assaulting loads such as blast on the human head. Finite Elements (FEs) can approximately simulate blast interactions with the human head. An important parameter in the FE modelling procedures is the accuracy of constitutive formulation of the brain tissue. This paper focuses on implementation of three brain tissue constitutive relations to measure and compare the dynamic behaviour of the brain under identical blast loads. For the geometry, a simple sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A Traumatic Brain Injury (TBI) may occur when induced stresses exceed the tolerance limits. In most biomechanical studies on human concussions, the attempts are focused on relating the size of the mechanical assault to the localized tissue deformation, pressure, and stressstrain response in order to diagnose the brain injury [1][2][3][4][5][6]. In such e orts, accurate measurement of generated stresses in the brain tissue is necessary for predicting the size of the injuries.…”
Section: Introductionmentioning
confidence: 99%
“…A Traumatic Brain Injury (TBI) may occur when induced stresses exceed the tolerance limits. In most biomechanical studies on human concussions, the attempts are focused on relating the size of the mechanical assault to the localized tissue deformation, pressure, and stressstrain response in order to diagnose the brain injury [1][2][3][4][5][6]. In such e orts, accurate measurement of generated stresses in the brain tissue is necessary for predicting the size of the injuries.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, scholars have proposed multiple brain models to account for particular features of brain tissue response under specific loading conditions and testing regimes [ 4 ]. Various constitutive material models suited for a particular type of brain tissue analysis are often referred to in the literature and are still developed [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Many studies have shown that soft tissues exhibit properties that are difficult to describe with rheological relations, assuming linear elasticity or viscoelasticity, because their characteristics may be highly nonlinear [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although their results are valid to be employed for studies in quasistatic loading, those material properties have been used in many computational simulations of TBI at dynamic loads [39,40]. It was confirmed [16,41] that, in addition to selecting an appropriate constitutive model, using the material constants derived from a mismatched strain rate may considerably affect the validity of the results. Farid et al [16] showed that hyper-viscoelastic material models, which are optimized for various low strain rates, will result in considerable errors when predicting brain behavior at higher strain rates.…”
Section: Introductionmentioning
confidence: 99%